A comparison of three adaptive psychophysical procedures using inexperienced listeners - Stillman, J A (Perception & psychophysics, 1989)
Thresholds for a masked 1-kHz tone were obtained in single sessions from 60 inexperienced listeners. A two-alternative forced-choice procedure was used in conjunction with one of three adaptive psychophysical techniques. These techniques comprised two staircase techniques targeting either 70.7% or 79.4% correct detection (Staircase-71 and Staircase-79), and parameter estimation by sequential testing (PEST), targeting 80% correct detection. Listeners were provided with a rationale for maintaining concentration at weak signal levels. Similar threshold values were obtained from the Staircase-79 and PEST groups in equal numbers of trials. The degree of oscillation in the level of the signal around the value finally chosen as the threshold was comparable for both staircase techniques. Subsequent fixed-level testing did not provide a true indication of the subjects' capabilities. The amount by which percent correct in fixed-level testing differed from expectations based on adaptive testing varied among the techniques. Additional thresholds were obtained in a second session from 30 of the original subjects. Thresholds with both staircase techniques improved by about 1 dB on retest, while thresholds with PEST were constant across sessions. The variability of the data compared well with that from studies involving experienced listeners.